Recent Advances in Liposomal-Based Anti-Inflammatory Therapy - van Alem, Carla M. A. (Pharmaceutics, 2021)
Liposomes can be seen as ideal carriers for anti-inflammatory drugs as their ability to (passively) target sites of inflammation and release their content to inflammatory target cells enables them to increase local efficacy with only limited systemic exposure and adverse effects. Nonetheless, few liposomal formulations seem to reach the clinic. The current review provides an overview of the more recent innovations in liposomal treatment of rheumatoid arthritis, psoriasis, vascular inflammation, and transplantation. Cutting edge developments include the liposomal delivery of gene and RNA therapeutics and the use of hybrid systems where several liposomal bilayer features, or several drugs, are combined in a single formulation. The majority of the articles reviewed here focus on preclinical animal studies where proof-of-principle of an improved efficacy–safety ratio is observed when using liposomal formulations. A few clinical studies are included as well, which brings us to a discussion about the challenges of clinical translation of liposomal nanomedicines in the field of inflammatory diseases.